Study of service in young volleyball players, taking into account efficacy and role play - *Alexander Gil Arias, *M. Perla Moreno Arroyo, *Alberto Moreno Domínguez, **Luís García González, *Fernando Del Villar Álvarez (FEADEF, 2011)
The main objective of this study was to analyze the volleyball serve formative stages based on the function punch game player and receiver, and its effectiveness, and also establishing partnerships between these variables and gender. To this end, we analyzed a total of 1827 shares belonging to pull Spain Championship regional selections cadet class of 2005. The results show that both boys and girls guide to serve the ball to other players who are neither attackers-front, or underwriters, or releasing. However, the variable effectiveness, predominate in children serves to permit the construction of multiple attacks, while girls performed serves to limit the options of building the attack. In the inferential analysis, the gender variable is significantly associated with the three variables considered in the investigation, where the completion of the service by receptor-bombers and effectively services 1 and 0 are associated significantly and positively with male gender while carrying out the services from the opposite and the central and efficacy 3 and 4 are associated significantly and positively with the female gender.